Rotational flywheel training in youth female team sport athletes: could inter-repetition movement variability be beneficial? - Arede, J.; Gonzalo-Skok, O.; Bishop, C.; Schöllhorn, W. I.; Leite, N. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The aim of this study was to analyze the effects of an inter-repetition variable rotational flywheel training program (variable) over standard rotational flywheel training (Standard). METHODS: Twenty-four youth female team-sports players were randomly assigned to both training groups (variable, N.=12; standard, N.=12), which consisted of 1 set of 3 rotational flywheel exercises ×10-12 repetitions, biweekly for a period of 6-weeks. The participants included in variable group were instructed to perform the movement randomly in one of the three directions (0°, 45° right, and 45° left). Measurements included reactive strength, jumping, change of direction, and sprinting tests; patellar tendon condition was also assessed. RESULTS: Substantial improvements were found in vertical jump with left leg (16.9%), lateral jump with right leg (13.6%), and patellar condition in left leg (4.1%) for standard group, but also in reactive strength index in right leg landing (33.9%), vertical jump with right (10.1%) and left leg (12.0%) for variable group. A significant interaction effect (group × time) was observed on patellar condition in right leg (F=10.02, P<0.01, Eta²=0.37), favoring variable group. CONCLUSIONS: Rotational flywheel training programs were beneficial for youth-female team-sports athletes, although the movement variability may play a key role to develop different and specific physical adaptations.